Combined Use of Emodin and Ginsenoside Rb1 Exerts Synergistic Neuroprotection in Cerebral Ischemia/Reperfusion Rats - Yan Li; Qing-qing Xu; Chun-shuo Shan; Yi-hua Shi; Yong Wang; Guo-qing Zheng (Frontiers Media S.A., 2018)
Acute ischemic stroke (AIS) generally causes neurological dysfunction and poses a serious threat to public health. Here, we aimed to assess the independent and combined effects of ginsenoside Rb1 (GRb1) and Emodin on neuroprotection through regulating Connexin 43 (Cx43) and Aquaporin 4 (AQP4) expression in cerebral ischemia/reperfusion (I/R) model rats. Adult male Sprague-Dawley (SD) rats were randomly divided into five groups: sham group, I/R group, Emodin group, GRb1 group and Emodin+GRb1 group. They were further allocated to four subgroups according to the 6h, 1d, 3d, and 7d time points except the sham group. Based on the modified Longa suture method, the focal cerebral I/R model was established by middle cerebral artery occlusion (MCAO). The neurological deficit scores (NDS), blood brain barrier (BBB) permeability and cerebral infarction area were assessed at each corresponding time point. Cx43 and AQP4 levels were assessed by Real-time PCR and Immunofluorescence. Compared with I/R group, both the independent and combined use of GRb1 and Emodin could alleviate NDS, reduce the BBB permeability, reduce the infarction area and down-regulate Cx43 and AQP4 expression at 6h, 1d, 3d, and 7d after I/R (P < 0.05). The Emodin+GRb1 group had more significant effects than Emodin group and GRb1 group (P < 0.05). In conclusion, the combination of Emodin and GRb1 exerts synergistically neuroprotective functions through regulating AQP4 and Cx43 after I/R.